2010
DOI: 10.1038/nm.2110
|View full text |Cite
|
Sign up to set email alerts
|

T helper type 1 and 17 cells determine efficacy of interferon-β in multiple sclerosis and experimental encephalomyelitis

Abstract: Interferon-β is the major treatment for multiple sclerosis (MS). However, this treatment is not always effective. Here we see congruence in outcome between responses to IFN-β in experimental autoimmune encephalomyelitis (EAE) and relapsing-remitting MS (RRMS). IFN-β is effective in reducing EAE induced by TH1 cells, but exacerbated disease induced by TH17. Effective treatment in TH1 EAE correlated with increased IL-10 in the spleen. In TH17 disease, the amount of IL-10 was unaltered by treatment, though unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
443
3
7

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 503 publications
(505 citation statements)
references
References 37 publications
41
443
3
7
Order By: Relevance
“…After treatment with αDEC205/PLP, splenocytes or lymph node cells were markedly anergic to PLP139-151 and had severely reduced IL-17 production but little or no change in IFNγ secretion. This experiment may reinforce the relative importance of IL-17 in the pathogenesis of EAE in this model system (31). A high level of Foxp3 + CD4 + Vβ6 + T cells was seen after treatment with control GL117 mAb, and no further increase was found after treatment with αDEC205/PLP.…”
Section: Discussionsupporting
confidence: 73%
“…After treatment with αDEC205/PLP, splenocytes or lymph node cells were markedly anergic to PLP139-151 and had severely reduced IL-17 production but little or no change in IFNγ secretion. This experiment may reinforce the relative importance of IL-17 in the pathogenesis of EAE in this model system (31). A high level of Foxp3 + CD4 + Vβ6 + T cells was seen after treatment with control GL117 mAb, and no further increase was found after treatment with αDEC205/PLP.…”
Section: Discussionsupporting
confidence: 73%
“…Moreover, the frequency of IFNγ-producing CD3 + cells in peripheral blood of MS patients is reported to correlate with the severity of disease in women but not men (16). Finally, analysis of MRI data from a large randomized trial of secondary progressive MS has indicated that women may be more responsive than men to IFNβ therapy (35), a treatment that may preferentially mitigate Th1 inflammation (36). If, indeed, these sex differences in Th cytokine production persist during autoimmune inflammation, it raises the prospect that women and men with MS should be treated differently.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties in this area are illustrated by recent work on IL-17 F, a cytokine highly expressed by Th17 cells. Based on initial work in EAE in rats, which indicated the presence of Th17 cells corresponded to worsened disease scores [66], Axtell et al retrospectively analyzed 26 patients with RRMS on IFNB and found that elevated pretreatment levels of IL-17 F were present in patients who were poor responders to the IFNBs. In an attempt to replicate these results, Bushnell et al [67] used 118 samples from an IFNB-1a IM dose comparison study and reanalyzed the samples from Axtell et al [66], using very similar methods and a comprehensive assessment for quality.…”
Section: Biomarkersmentioning
confidence: 99%